Long-term clinical outcomes after bilateral implantation of two trifocal diffractive IOLs - Khoramnia, Ramin; Kretz, Florian Tobias Alwin; Gerl, Matthias; Breyer, Detlev Richard Hans; Auffarth, Gerd U. (Journal of refractive surgery, 2023)
PURPOSE: - - To show clinical outcomes after bilateral implantation of either a hydrophobic FineVision POD F GF or a hydro-philic FineVision POD F intraocular lens (IOL) (Beaver-Visitec International, Inc). - - METHODS: - - A total of 110 patients with cataract were randomized to receive either POD F GF or POD F IOLs and followed up for 2 years. The measurements included refraction, monocular and binocular uncorrected and corrected distance (UDVA and CDVA), intermediate (UIVA and DCIVA), and near (UNVA and DCNVA) visual acuities, defocus curve, photopic and mesopic contrast sensitivity, photic phenomena, and patient-reported outcomes. - - RESULTS: - - The mean spherical equivalent was similar in both groups and stable across visits (< 0.25 diopters [D]). At 2 years, 81.8% and 90.5% of eyes were within ±0.50 D in the POD F GF and POD F IOL groups, respectively (100% for ±1.00 D in both groups). At 2 years, 100% and 90.5% of the patients presented a binocular CDVA of 20/25 or better; 93.9% and 85.7% of patients a DCIVA of 20/25 or better and 87.5% and 70% of patients a DCNVA of 20/25 or better, for the POD F GF and POD F IOL groups, respectively. The defocus curve showed continuous visual acuity, being 20/32 or better in both groups over a 4.50 D range. Both groups presented good contrast sensitivity for photopic and mesopic conditions, and the size and intensity of halo and glare phenomena were similar between the two. Both groups also included a high percentage of patients who reported that they had stopped wearing glasses and greater than 80% satisfaction and recommendation levels. - - CONCLUSIONS: - - This study showed comparable long-term visual and refractive outcomes of both IOL models after cataract surgery. - - [J Refract Surg. 2023;39(12):798-807.]
Gesehen am 08.03.2024